Men’s knowledge about osteoporosis and its risk factors - Janiszewska, Mariola; Żołnierczuk-Kieliszek, Dorota; Kulik, Teresa; Dziedzic, Małgorzata A.; Barańska, Agnieszka; Kryk, Aneta (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction : Until recently osteoporosis was seen mainly as a woman’s problem. However, in the last ten years there has been rising awareness in society that osteoporosis constitutes an inseparable element of getting old for men as well. The aim of the research was to evaluate men’s knowledge about osteoporosis and its risk factors contributing to the development of the disease. Material and methods: The study included 205 men aged 20-60. The examined men were patients of selected healthcare centres in Lublin Voivodeship. The study was conducted between September 2014 and April 2015. The research was performed by means of the survey method, using a poll technique. Purposive sampling and an original questionnaire were used. Gathered material was subjected to descriptive and statistical analysis. The Mann-Whitney U test and Kruskal-Wallis test were applied. The statistical significance level was set at = 0.05. IBM SPSS Statistics software was used to perform the statistical analysis. Results : The respondents’ level of knowledge about osteoporosis and its risk factors can be estimated as average. The polled men showed better knowledge on osteoporosis risk factors (M = 59.78) than general osteoporosis knowledge (M = 53.71). Significant differences were found between the respondents’ education and their general osteoporosis knowledge as well as between the respondents’ living conditions and their knowledge about osteoporosis risk factors. Conclusions : Because of the insufficient level of knowledge about osteoporosis and its risk factors in the male population it is advisable to launch prevention programmes aimed at men focusing on this issue.